Blockchain applications in IoT security - Patel, Harshita, 1985-; Thakur, Ghanshyam Singh, 1976- (Advances in information security, privacy, and ethics (AISPE) book series., 2021)
"This book examines the role of blockchain technology in IoT generated data security issues"--